a) 3 1/3x + 16 3/4 = -13,25
10/3x + 67/4 = -53/4
10/3x = -53/4 - 67/4
10/3x = -120/4
10/3x = -30
x = -30:10/3
x = -9
b) (2 1/5 + 3/5x) = 3/4
(11/5 +3/5x) = 3/4
3/5x = 3/4 - 11/5
3/5x = 15/20 - 44/20
3/5x = -29/20
x = -29/20:3/5
x = -29/20.5/3
x = -29.5/20.3
x = -29.1/4.3
x = -29/12
c) (2,4x - 36) : 1 5/7 = -1
(12/5x - 36) : 12/7 = -1
(12/5x - 36) = -1.12/7
(12/5x - 36) = -12/7
12/5x = -12/7+36
12/5x = -12/7+252/7
12/5x = 240/7
x = 240/7:12/5
x = 240/7.5/12
x = 100/7
d) 5/6 - x = -7/12 + 2/3
5/6 - x = -7/12 + 8/12
5/6 - x = 1/12
x = 5/6 - 1/12
x = 10/12 - 1/12
x = 9/12
x = 3/4
a/ 1/2 + 3/4 + 5/8
= 4/8 + 6/8 +5/8
=4+6+5/8
=15/8
b/ -3/4.4/7 + -3/5.3/7 + 2/-5
= (-3/4.4/7) + (-3/5.3/7) + 2/-5
= -3/7 + -9/35 + 2/-5
= -3/7 + (-9/35) + (-2/5)
= (-3/7+ -9/35) + (-2/5)
= (-15/35+ -9/35) + (-2/5)
= -24/35 + (-2/5)
= -24/35 + (-14/35)
= -38/35
c/ (3/4 - 5/6 + 7/12).(-12/7)
= (9/12 - 10/12 + 7/12).(-12/7)
= 6/12.(-12/7)
= 1/2.(-12/7)
= -6/7
d/ 1,4.15/49 - (4/5 + 2/3): 2 1/5
= 7/5.15/49 - (12/15 + 10/15): 11/5
= 3/7 - 22/15: 11/5
= 3/7 - 22/15.5/11
= 3/7 - 22.5/15.11
= 3/7 - 2.1/3.1
= 3/7 - 2/3
= 9/21 - 14/21
= -5/21